2016
DOI: 10.1097/md.0000000000005184
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of paroxysmal atrial fibrillation on plasma markers of fibrinolysis

Abstract: There are no studies to date on the early changes in the hemostasis profile of patients with paroxysmal atrial fibrillation (PAF).Given the key role of the fibrinolytic system in maintaining blood fluidity, our aim was to examine its activity in patients with clinical manifestation of the disease <24 hours.We studied 51 nonanticoagulated patients with a first episode of the disease (26 men, 25 women; mean age 59.84 ± 1.60 years) and 52 controls (26 men, 26 women; mean age 59.50 ± 1.46 years) who matched the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…In our clinical trial of PAF patients, we found significant changes in major indicators of fibrinolysis as early as the first twenty-four hours of the clinical manifestation of the arrhythmia (Table 1) [10].…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In our clinical trial of PAF patients, we found significant changes in major indicators of fibrinolysis as early as the first twenty-four hours of the clinical manifestation of the arrhythmia (Table 1) [10].…”
mentioning
confidence: 79%
“…The fibrinolytic parameters were examined in peripheral venous blood. The samples were collected, centrifuged and the resulting citrate plasma stored according to the requirements of the tests used, which have been described in detail elsewhere by us [10]. The indicators were determined using colorimetric and enzyme-linked immunosorbent assays [10].…”
Section: Blood Sample Collection and Laboratory Proceduresmentioning
confidence: 99%
“…7 Multiple studies have also noted this biomarker's utility in AF as an indicator of left atrial enlargement, thrombus formation, and cardiac stress. [8][9][10] Overall, while not clinically relevant in AF, the D-dimer test seems to be an indicator of the prothrombotic atmosphere created by AF. Therefore, we included this biomarker in our study to investigate its role in PE patients with comorbid AF.…”
Section: D-dimermentioning
confidence: 99%
“…Negreva et al reported that PAI-1 activity is lower in patients with paroxysmal AF compared with control patients suggesting that there is high plasma fibrinolytic activity even during the first 24 hours of the disease. 52 Gramley et al observed that with increasing duration of AF, PAI-1 expression decreases, which they attributed to increased atrial fibrosis. 53 Years before even hypothesizing of mechanism for AF's relationship with PAI-1, Pretorius et al reported that perioperative PAI-1 levels can be predictive of developing postoperative AF in patients undergoing coronary artery bypass surgery.…”
Section: Plasminogen Activator Inhibitor-1mentioning
confidence: 99%